Biosynthesis and Characterization of ZnO Nanoparticles with Extract of Green Seaweed Caulerpa sp. - Rodiah Nurbaya Sari; Nanda Saridewi; Shofwatunnisa Shofwatunnisa (Universitas Gadjah Mada, 2017)
Biosynthesis and characterization of ZnO Nanoparticles by the reduction method have been performed. This study aims to determine the ability of Caulerpa sp. as a reducing agent and stabilizer. Extract Caulerpa sp. was reacted with Zn(CH3COO)2.2H2O solution in variation concentration of 0.05, 0.1, and 0.15 M and the pH of the solution was conditioned with NaOH 0.1 M added became 7, 8, 9. Characterization of ZnO nanoparticles was performed for functional group analysis (FTIR), surface morphology and particle distribution (SEM), knowing the phase type (XRD), and particle size and particle size (PSA). The result of phase analysis by XRD shows that the synthesis of ZnO nanoparticles using green seaweed extract Caulerpa sp. has been successfully performed with the formation of the optimum ZnO nanoparticles 0.15 M at pH 8. The ZnO nanoparticles had a relatively similar particle size distribution with an average particle size of 370.72 nm. Based on FTIR results it was known that the compound suspected to act as a bioreductor and stabilizer agent in the synthesis of ZnO nanoparticles was a protein